(untitled) (Veterinary Science, 2017)
The beef cattle production system in the east area of Caldenal tends to concentrate the parturition in a short period of time, adjusting the availability of forage production with the maximum nutrient herd demando Nevertheless the current system has the main disadvantage to offer weaning calf in a tiny period of time affecting negatively both the sale price and the provision of animal to feed lot that demand animal year round. The objective of the project was to develop a new methodology to distribute the calving around the year in arder 10 increase the economic and reproductive efficiencies . It was chosen six beef herd on native pasture in the Caldenal area with strategic energy supplementation. The breeding season was planned to be of 90 days of duration, where the last 30 days of breeding of the initial herd mach with the first 30 days of the fol1owing. The percentage of calving detected by the alternative method were the same or higher to those observed by the traditional system